2010
DOI: 10.2202/1932-0205.1238
|View full text |Cite
|
Sign up to set email alerts
|

Financial Regulation in Hong Kong: Time for a Change

Abstract: The global financial system experienced its first systemic crisis since the 1930s in autumn 2008, with the failure of major financial institutions in the United States and Europe and the seizure of global credit markets. Although Hong Kong was not at the epicentre of this crisis, it was nonetheless affected. Following an overview of Hong Kong's existing financial regulatory framework, the article discusses the global financial crisis and its impact in Hong Kong, as well as regulatory responses to date. From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Under the ordinance, the SFC is an independent statutory body that regulates the securities and futures markets in Hong Kong (Arner et al. ; HKEx ). Another reform was the restructuring of the Council of the Hong Kong Stock Exchange in 1991.…”
Section: Stock Market Development In Hong Kongmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the ordinance, the SFC is an independent statutory body that regulates the securities and futures markets in Hong Kong (Arner et al. ; HKEx ). Another reform was the restructuring of the Council of the Hong Kong Stock Exchange in 1991.…”
Section: Stock Market Development In Hong Kongmentioning
confidence: 99%
“…Under the ordinance, the SFC is an independent statutory body whose task is to regulate the securities and futures markets in Hong Kong (Arner et al. ).…”
Section: Stock Market Development In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after the collapse of Lehman Brothers, Hong Kong still lacks a comprehensive compensation scheme, which includes a special crisis management mechanism to deal with banks or financial groups' failure (Arner et al, 2010). Therefore, it is suggested that Hong Kong should take initiative in improving the financial regulatory structure with respect to the international standard, rather than taking a reactionary approach as a result of crisis ).…”
Section: Hong Kong Financial Regulation: Necessity Of Bank Crisis Manmentioning
confidence: 99%
“…This implication can also apply in cross-border bank insolvency. Even though Hong Kong has close relationships with international organizations, such as Financial Stability Board and Basel Committee on Banking Supervision, Arner (2010) points out that Hong Kong still lacks crisis management scheme for banks, as well as highlights the weakness of the deposit insurance scheme in dealing with failure of financial institutions.…”
Section: Introductionmentioning
confidence: 99%